Treatment before transfer: the patient with burns. Issue 5 (1st September 2001) - Ashworth, H L; Cubison, T C S; Gilbert, P M; Sim, K M
Abstract : Objectives —To review pre-burns centre management, including assessment, resuscitation, and transfer. Methods —A retrospective analysis of the notes of all the UK patients admitted to the Burns Centre in 1998, who had a body surface area burn of over 15% in adults (10% in children). Results —There were 31 patients, 21 adults and 10 children, and the average burn size was 32% (12–96%). Fourteen were overestimated (average of 9%) and 13 underestimated by 7.5%. Twenty nine received intravenous fluids, 18 specified a formula, but it was only applied correctly in 10. The average time to the Burns Centre from the burn was 10 hours, and the time for resuscitation and transfer, eight hours. Documentation was generally poor. Conclusion —There has previously been considerable variation in the standard of initial burn management and there have been problems with burn percentage assessment and resuscitation formula application. A new proforma has been introduced to tackle these issues.